10 Screening of neuropsychiatric symptoms in patients with parkinson's disease in a uk general practice. Issue 8 (13th July 2017) - Cronin, Thomas; Gallagher, Sean
Abstract : Objective: Neuropsychiatric symptoms are common in Parkinson's disease (PD) and have important consequences for quality of life and daily functioning. Amongst the most frequent are dementia, depression, anxiety and psychosis. By contrast with the motor symptoms of PD, these problems are often poorly recognised and inadequately treated. The first step towards their management is identification. Therefore, a service evaluation was undertaken, at a UK general practice, with the aim to identify the proportion of patients who are screened for the common neuropsychiatric manifestations of PD. Method: The electronic medical records of 12 915 registered patients at one UK general practice were searched for read codes relating to PD and dopaminergic drug use. This identified twelve patients with a diagnosis of idiopathic PD. The notes of these patients were then reviewed to determine whether any form of screening had taken place in the last year regarding dementia/cognitive impairment, depression, anxiety, sleep disturbance and hallucinations. Results: In the last year, 83% (n=10) of identified patients had seen a GP. For these patients, the average number of visits was 5.4 range 2–11). Screening in relation to dementia was documented in 1 patient, to depression in 2 patients, to anxiety in patients, to sleep in 2 patients and to hallucinations in 1 patient. Conclusion: In patients who had visited their GP in the last year, there was a low proportion of documented screening for the common neuropsychiatric symptoms occurring in PD. Although these patients may not be consulting about issues relating to PD, given the significance of neuropsychiatric symptoms, opportunistic screening should be considered. A presentation of these results has been delivered to the GPs at this practice and a service evaluation will be performed again next year.